Analisis Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja di Kota Jambi - Putri, Ersanti Laras Eka; Zulfanetti, Zulfanetti; Umiyati, Etik (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims for analyzing the influence of the average length of study at school , minimum wage , number of company , Gross Regional Domestic Product (GRDP) and Domestic Investment (DI) on the absorption of labor in Jambi City. The data used in this study is secondary data in coherent time from 2000 to 2021 derived from Institute of Statistics Centre (ISC). Method analysis used in this research is analysis of quantitative multiple linear regression . The result study shows that the average length of schooling is positively influenced and leads to negative significant to absorption of labor. The minimum wage is positively and significantly influenced and to absorption of labor. Domestic Invesyment (ID) is positively and significantly influenced to absorption of labor.Gross Regional Domestic Product (GRDP) and numner of company have no influence to absorption of labor.